The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18046/j.estger.2019.151.3192
|View full text |Cite
|
Sign up to set email alerts
|

El liderazgo transformacional y su influencia en los atributos de los seguidores en las Mipymes mexicanas

Abstract: La presente investigación busca analizar y explicar la influencia del liderazgo transformacional en los atributos de los seguidores de las Mipymes de Durango (México). Para esto, se aplicó un cuestionario a una muestra de líderes y sus seguidores de 360 empresas escogidas al azar. Con base en la información recopilada se construyeron 84 modelos de regresión lineal, encontrando evidencia estadísticamente significativa de la influencia del liderazgo transformacional en los atributos de los seguidores. El factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
3
0
10
Order By: Relevance
“…In a recent study, Zárate-Torres et al (2022) reported the scarcity of Latin-American studies focusing on the relationship between personality, gender, and leadership. Likewise, Chacón-Henao et al (2022) reported that in emerging Latin-American countries such as Colombia, leadership studies have focused mainly on particular attributes and styles of individual leaders (Hincapié-Montoya et al, 2018;Reyes Bastidas and Briano-Turrent, 2018;Gaviria-Rivera and López Zapata, 2019;Rojero-Jiménez et al, 2019). We regard these recent studies as evidence that shows how leadership studies in Colombia and Latin America countries deserve additional local efforts to unveil how leadership and personality proved to be linked when using tools such as the MBTI and the LPI.…”
Section: The Impact Of Personality On Leadershipmentioning
confidence: 95%
“…In a recent study, Zárate-Torres et al (2022) reported the scarcity of Latin-American studies focusing on the relationship between personality, gender, and leadership. Likewise, Chacón-Henao et al (2022) reported that in emerging Latin-American countries such as Colombia, leadership studies have focused mainly on particular attributes and styles of individual leaders (Hincapié-Montoya et al, 2018;Reyes Bastidas and Briano-Turrent, 2018;Gaviria-Rivera and López Zapata, 2019;Rojero-Jiménez et al, 2019). We regard these recent studies as evidence that shows how leadership studies in Colombia and Latin America countries deserve additional local efforts to unveil how leadership and personality proved to be linked when using tools such as the MBTI and the LPI.…”
Section: The Impact Of Personality On Leadershipmentioning
confidence: 95%
“…Según Hincapié Montoya, Zuluaga Correa y López Zapata, 70 este liderazgo se basa en desarrollar y aumentar los niveles de autoestima de los seguidores y el líder, para generar resultados positivos en la entidad, a través de factores como la efectividad, motivación y satisfacción. Esto coincide con lo dicho por Rojero Jiménez, Gómez Romero y Quintero Robles, 71 que este estilo de liderazgo se caracteriza por incitar a los seguidores a aumentar el nivel de desempeño y grado de fidelidad con la entidad, además de mejorar sustancialmente el trabajo en equipo y la cooperación entre líder y seguidores. Por lo que se recomienda para próximos estudios, realizar evaluaciones a cada uno de los líderes que forman parte de las agencias de la entidad financiera de Imbabura Ecuador, donde se puedan evidenciar las características principales que poseen.…”
Section: Discusión Y Conclusionesunclassified
“…72 Kolnhofer-Derecskei, Reicher y Szeghegyi, "The X and Y…", 107-125. 73 Stewart et al,"Managing Millennials…",[45][46][47][48][49][50][51][52][53][54]"Formulación…",[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]Rauvola y Zacher,"Leadership and Generations…",[44][45][46][47][48][49][50][51][52][53][54][55][56][57]…”
Section: Discusión Y Conclusionesmentioning
confidence: 99%
“…Leadership represents a social and complex phenomenon of great interest (Londoño-Proaño, 2022;Gómez-Romero & Quintero-Robles, 2019;Fernández & Quintero, 2017;Ramírez Méndez, 2013cited by Rojero-Jiménez et al, 2019 that has evolved to the same as the nature of the human being (Emeka, 2022). It is analyzed as a process of social influence (Zárate-Torres et al, 2022) and exercised by individuals who have qualities that contribute to organizational management tasks (Jauregui-Arroyo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%